David Slays Goliath: Exceptional Efficacy of Oral Vinorelbine in Conquering Metastatic Finger Angiosarcoma - Te-Lin Hsu; San-Chi Chen (Journal of Cancer Research and Practice)
Angiosarcoma (AS) is a rare and aggressive disease originating from blood or lymphatic vessel endothelium, representing <1% of soft-tissue sarcomas. The prognosis is generally poor, with a 5-year survival rate of only 30%–50%. The recurrence rate is high, and metastasis occurs in about half of the cases. The National Comprehensive Cancer Network guidelines recommend anthracycline-based, gemcitabine-based, and paclitaxel regimens as preferred first-line treatments for metastatic AS. Vinorelbine, a vinca alkaloid, is listed as supportive care in AS for patients unsuitable for intensive chemotherapy or who are heavily treated. Although the efficacy of vinorelbine is modest, some studies suggest its synergistic effect with immunotherapy. In our case report, a patient with metastatic AS received frontline paclitaxel followed by pembrolizumab, but this treatment failed. However, a complete response (CR) was achieved after oral vinorelbine. Remarkably, the patient remains in CR for 4.5 years after discontinuing vinorelbine.